THE IMPOSSIBILITY OF PRESCRIBING THE TRANSFER OF TITLE IN ACQUISITIVE PRESCRIPTION - Bravo Chacón, Francisco (2025)
This document aims to carry out a study on the two denominations of the Costa Rican civil code, the transferable title and just title. This in order to determine if they are synonymous or if there is a difference between both terms worthy of recognition and that can cause the disuse of the figure of the transferable title. From this, we will seek to prove its importance and the reason why this figure cannot be dispensed with in practice at the time of acquiring a property.